To rearrange the slope formula \(y = mx + b\) for the quantity of interest \(m\), follow these steps:
-
Start with the original equation:
\[ y = mx + b \]
-
Subtract \(b\) from both sides to isolate the term containing \(m\):
\[ y - b = mx \]
-
Next, to solve for \(m\), divide both sides by \(x\) (assuming \(x \neq 0\)):
\[ \frac{y - b}{x} = m \]
-
Finally, rewrite the equation to present \(m\) clearly:
\[ m = \frac{y - b}{x} \]
Now, \(m\) is isolated, and the rearranged formula for the slope is:
\[ m = \frac{y - b}{x} \]